2007
DOI: 10.1111/j.1468-2508.2007.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Crisis, Charisma, and Consequences: Evidence from the 2004 U.S. Presidential Election

Abstract: We investigate how conditions of crisis affect perceptions of charisma and how these, in turn, affect blame attribution and self-sacrificial behavior. Our data are from a 2004 experimental study that preceded the U.S. presidential election, in which we manipulated concerns of a terrorist attack. The results show that those in the Crisis condition rated Bush higher on perceptions of charisma compared to those in the Good Times condition. The Crisis condition also directly and indirectly, via perceptions of char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 50 publications
0
76
0
Order By: Relevance
“…For example, scholars of TMT have found that individuals primed to think about 9/11 perceived Bush as a stronger leader than those in a control group (Landau et al 2004). In other work, we have shown that making terrorism salient through a media presentation caused subjects to project charisma onto George W. Bush (Merolla et al 2007). While the posited mechanism differs across studies, the end result is similar in that crises cause individuals to project relevant traits onto a person they deem capable of rescuing them from the crisis situation.…”
Section: Threat Leadership and Vote Choicementioning
confidence: 88%
See 1 more Smart Citation
“…For example, scholars of TMT have found that individuals primed to think about 9/11 perceived Bush as a stronger leader than those in a control group (Landau et al 2004). In other work, we have shown that making terrorism salient through a media presentation caused subjects to project charisma onto George W. Bush (Merolla et al 2007). While the posited mechanism differs across studies, the end result is similar in that crises cause individuals to project relevant traits onto a person they deem capable of rescuing them from the crisis situation.…”
Section: Threat Leadership and Vote Choicementioning
confidence: 88%
“…The Fall 2004 study design and manipulation check are also reported inMerolla et al (2007); we draw on that discussion here.…”
mentioning
confidence: 96%
“…An article in Business Week (Smith, 2006) suggested that "Vicente Fox won the Mexican presidency in 2000 by using his charisma and marketing savvy to sell himself as an agent of change and the country's best hope of booting the corrupt Institutional Revolutionary Party [PRI] -in power for seven decades -from office" (p. 8). Merolla, Ramos, & Zechmesiter (2006) experimentally manipulated crisis (terrorist attack) prior to the 2004 elections and found that subjects in the "crisis" condition rated President Bush significantly higher on charisma than subjects in the "good times" condition. Halverston, Murphy, & Riggio (2004) also experimentally manipulated stress conditions and found that leaders of groups in the stress condition were perceived as significantly more charismatic than leaders in the no-stress condition.…”
Section: Crisis and Charismamentioning
confidence: 98%
“…1111(Weber, -1112(Weber, , 1117Roberts & Bradley, 1988;Bryman, 1992, pp. 54-55;Merolla et al, 2007). However, in both cases treated here, the crisis took the form of an ongoing or imminent change that was perceived as intimidating to the group and its values and interests.…”
Section: Cross-case Analysismentioning
confidence: 76%
“…This applies to the important role of followers in enabling charisma (Howell & Shamir, 2005) and to the charisma-inducing effects of crises (Bligh, Kohles & Meindl, 2004;Merolla, Ramos & Zechmeister, 2007), powerful oratory and rhetorical devices (Awamleh & Gardner, 1999;Mio, Riggio, Levin & Reese, 2005), and leader self-sacrifice (Choi & Mai-Dalton, 1999;Halverson, Holladay, Kazama & Quiñones, 2004).…”
Section: Introductionmentioning
confidence: 95%